A Confrontation on Gwendolyn Willow Wilson’s Alif The Unseen: A Study of Postmodernism - Ninik Afriani; Endang Suciati (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2018)
AbstractThis project aims to give an analysis of the signs of confrontation in terms of postmodernism strategies by Brian McHale experienced by the main character in Gwendolyn Willow Wilson’s Alif The Unseen. Besides, the researcher analyzed the novel used the theory by Jean Francois Lyotard and Fredrich Jameson to describe the main character’s reaction toward ontological confrontation in postmodern society used in the novel. This article is qualitative research which used the Postmodernism studies to understand one of the strategies to show the ontological confrontations in the novel. This article elaborated some ontological confrontations in postmodernism including confrontation between the fiction and the historical realemes, the fusion between two worlds, and also polyglot. Meanwhile, this article also classified the main character’s reaction toward the ontological confrontation in 5 reactions: refusal reaction, skeptical reaction, curiousity reaction, surprise reaction, and acceptance reaction. It can be concluded that Alif as the part of Postmodern society must recognized the jinn creatures around him as the hacker who has the high ability and dependency of the technology.Keywords: Confrontation, Alif The Unseen, Postmodernism AbstrakPenelitian ini bertujuan untuk memberikan analisis terhadap tanda-tanda konfrontasi dalam hal strategi postmodernisme oleh Brian McHale yang dialami oleh tokoh utama dalam Alif The Unseen karya Gwendolyn Willow Wilson. Selain itu, peneliti menganalisis novel menggunakan teori oleh Jean Francois Lyotard dan Fredrich Jameson untuk menggambarkan reaksi karakter utama terhadap konfrontasi ontologis dalam masyarakat postmodern yang digunakan dalam novel. Penelitian ini merupakan penelitian kualitatif yang menggunakan studi Postmodernisme untuk memahami salah satu strategi untuk menunjukkan konfrontasi ontologis dalam novel. Artikel ini menguraikan beberapa konfrontasi ontologis dalam postmodernisme termasuk konfrontasi antara fiksi dan kenyataan sejarah, fusi antara dua dunia, dan juga polyglot. Sementara itu, artikel ini juga mengklasifikasikan reaksi karakter utama terhadap konfrontasi ontologis dalam 5 reaksi: reaksi penolakan, reaksi skeptis, reaksi rasa ingin tahu, reaksi kejutan, dan reaksi penerimaan. Dapat disimpulkan bahwa Alif sebagai bagian dari masyarakat Postmodern harus mengakui makhluk jin di sekitarnya sebagai peretas yang memiliki kemampuan tinggi dan ketergantungan teknologi.Kata kunci: Konfrontasi, Alif The Unseen, Postmodernisme